MARKET REACTION ON PT GARUDA INDONESIA DEBT RESTRUCTURING ANNOUNCEMENTS - Fauziah, Fitri Ella; murharsito, murharsito (Jurnal Akuntansi, 2025)
Corporate debt restructuring is a meaningful mechanism for firms in supervising their financial challenges. This study examines the market reaction to debt restructuring announcements by PT Garuda Indonesia, a prominent Indonesian airline facing financial distress. The research employs an event study methodology, analyzing stock price movements 7 days before and after key restructuring announcements. Data was collected from the Indonesia Stock Exchange (IDX). The method employed in this study was the Shapiro-Wilk to test the normality and paired sample t-test to test the hypothesis. The results show a significant difference in stock prices for the announcements on December 30, 2020 and December 29, 2023. These results provide implications that the market can provide a positive response or provide appreciation for corporate debt restructuring events as in the case of PT Garuda Indonesia. This study provides an understanding of market efficiency and the impact of corporate financial strategies related to debt issues that are still rarely found in the literature.